PROMPTa—A multifaceted assessment approach to develop writing skills - Vezolu Puro; Noel Anurag Prashanth Nittala; Hariharasudan A (PLoS ONE, 2025)
Assessment plays a pivotal role in developing writing skills, yet traditional teacher-led evaluations often fall short in addressing learner’s diverse needs, creating a substantial gap in effective writing methodologies. Lack of evidence-based studies to measure the effectiveness of assistive assessment technologies in a traditional setting, furthers the need for the study. The main objective of this study is to examine the effectiveness of PROMPTa (Performance Review of Manuscript Proficiency Tool for Assessment), a tool-based, ICT-integrated, multifaceted assessment framework that enables alternative assessment through peer, mentor and expert assessment and feedback, on improving learners’ writing performance. The study employed a mixed-methods approach, involving 143 first-year undergraduates, with 92 participants forming the final sample. Students were randomly assigned to an experimental group using PROMPTa for assessment, and a control group which followed traditional classroom evaluation. The experimental group demonstrated significant improvement, with higher post-test scores compared to the control group, resulting in a noticeable difference in the performance. These findings suggest that multifaceted peer-assisted ICT-based assessment tools like PROMPTa may significantly improve writing instruction strategies in higher education. This study not only adds to the existing literature and provides supporting evidence to technology-enhanced assessment approaches but also offers practical implications for educators who seek to improve the written performance of their students employing innovative methods of evaluation.